2011
DOI: 10.1200/jco.2011.35.4928
|View full text |Cite
|
Sign up to set email alerts
|

MET Amplification Identifies a Small and Aggressive Subgroup of Esophagogastric Adenocarcinoma With Evidence of Responsiveness to Crizotinib

Abstract: A B S T R A C T PurposeAmplification of the MET proto-oncogene in gastroesophageal cancer (GEC) may constitute a molecular marker for targeted therapy. We examined a GEC cohort with follow-up and reported the clinical response of four additional patients with MET-amplified tumors to the small molecule inhibitor crizotinib as part of an expanded phase I cohort study. Patients and MethodsFrom 2007 to 2009, patients with GEC were genetically screened as a consecutive series of 489 tumors (stages 0, I, and II, 39%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
379
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(406 citation statements)
references
References 41 publications
25
379
1
1
Order By: Relevance
“…Furthermore, 26% (24 of 93) of the amplifications were amplification of one of four genes (ERBB2, FGFR2, MET, and EGFR) that encode a RTK. The frequencies of these gene amplifications were not significantly different from those previously reported for ERBB2, FGFR2, 9,10,12,14 MET, 6,7,14,15 and EGFR. 6,20 It is intriguing that, except for case 7, RTK gene amplification occurred in a mutually exclusive manner.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Furthermore, 26% (24 of 93) of the amplifications were amplification of one of four genes (ERBB2, FGFR2, MET, and EGFR) that encode a RTK. The frequencies of these gene amplifications were not significantly different from those previously reported for ERBB2, FGFR2, 9,10,12,14 MET, 6,7,14,15 and EGFR. 6,20 It is intriguing that, except for case 7, RTK gene amplification occurred in a mutually exclusive manner.…”
Section: Discussioncontrasting
confidence: 76%
“…However, there is an urgent need for other inhibitors to be investigated for the therapy of many of the unique molecular subtypes of gastric cancer. 5 In particular, FGFR2 and MET, which encode RTKs similar to ERBB2, are considered as strong candidate targets because their amplification is associated with advanced stages, 6,7 and furthermore, the amplification of FGFR2 was preferentially found in a poorly differentiated subtype. 8,9 In preclinical studies, cells with amplified FGFR2 or MET showed overexpression of their respective proteins, and inhibitors to these receptors were shown to effectively block their downstream signal transduction and induce apoptosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,7,11,14,[16][17][18][19][20][21][22][23]33 Although MET expression showed poor prognostic effects on gastric carcinomas, 7,18,20,21,23 most studies were performed 410 years ago 5,7,17,[19][20][21][22] and interpreted either cytoplasmic or membranous positivity only 5,17-21 without considering intensity. In a recent large cohort study with gastric cancers with the same MET monoclonal antibody as ours, interpretation of membranous staining, which was used for HER2, failed to find any clinical significance and not all MET 3 þ cases exhibited amplification of MET gene.…”
Section: Discussionmentioning
confidence: 99%
“…As yet, there is no clinically validated method for defining cMET amplification, and thus the actual rate of amplification in tumour samples varies significantly between studies. The correlation between sensitivity to cMET-inhibitory agents and cMET amplification remains unclear, with various studies reporting correlation [48][49][50][51], transient sensitivity [52], or no correlation [53][54][55], and as such it will be important to define a method by which copy number can be accurately determined and clinically validated. In high grade serous ovarian cancer, the TCGA cBioPortal [56,57] reveals mutations in the Met gene to be present in 1.3% of cases, and amplifications in 1.6%.…”
Section: Mis-regulation Mechanisms Of Hgf/cmetmentioning
confidence: 99%